[Bmim][InCl4]-Catalyzed Addition of Hydrazones to β-Diketones: An Efficient Regioselective Synthesis of Pyrazoles and Pyrazole-Fused Cyclohexanones - Safaei, Shirin; Mohammadpoor-Baltork, Iraj; Khosropour, Ahmad Reza; Moghadam, Majid; Tangestaninejad, Shahram; Mirkhani, Valiollah; Khavasi, Hamid Reza (Synlett, 2013)
The Lewis acidic room-temperature ionic liquid, [bmim][InCl4], was found to be an efficient catalyst for the regioselective synthesis of fully substituted pyrazoles and pyrazole-fused cyclohexanones through condensation of hydrazones with symmetrical and unsymmetrical 1,3-diketones. This procedure is simple, affording the corresponding products in good to high yields.
Keywords: pyrazoles; arylhydrazones; Lewis acid room-temperature ionic liquid; regioselective